Carcass characteristics of sheep fed diets with slow-release urea replacing conventional urea - Alves, Evanilton Moura; Pedreira, Márcio dos Santos; Moreira, Beatriz Silva; Freire, Leile Daiane Ribeiro; Lima, Thiago Ramos; Santos-Cruz, Cristiane Leal dos (Acta Scientiarum. Animal Sciences, 2014)
This study aimed to evaluate the effects of adding slow-release urea to replace conventional urea in the diet on carcass characteristics of feedlot sheep. We used 20 Santa Ines x SRD rams, with average body weight of 21.1±1.2 kgand average age of 120 days, distributed in a completely randomized design with 5 treatments. The replacement levels used as treatments were 0, 20, 40, 60, and 80%, composing diets of about 12% crude protein, with 50 % Tifton-85 hay and 50% concentrate. There was no influence of slow release urea on weight at slaughter (35.17 kg), and on hot (16.75 kg) and cold (16.24 kg) carcass weight, but the yield of these carcasses showed quadratic trend, revealing lower percentages at 48.5 and 47.63% replacement levels, respectively. The weights and yields of cuts did not change, except for the posterior arm, whose values showed a cubic trend. Objective measures of carcass, loin eye area, and subjective evaluations of conformation, finishing and marbling of carcasses were not affected. The subcutaneous fat thickness decreased linearly (4.25 to2.48 mm). The inclusion of slow release urea in the diet changes the yield and reduces subcutaneous fat, however, it does not influence other carcass characteristics.